2011
DOI: 10.1038/eye.2011.268
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confocal microscopic evaluation of keratic precipitates and endothelial morphology in Fuchs’ uveitis syndrome

Abstract: Purpose To evaluate the endothelial cell layer in patients with Fuchs' uveitis syndrome (FUS) with respect to the type and distribution of keratic precipitates (KP), endothelial cell morphology, and endothelial cell density (ECD), using in vivo confocal microscopy (IVCM). Methods Forty eyes of 40 patients (mean age of 32.2 ± 12.5 years) with the clinical diagnosis of FUS were evaluated with IVCM (Confoscan 3.0, Vigonza, Italy). KP were classified as type I (small, round), type II (stippled), type III (dendriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
0
11
1
4
Order By: Relevance
“…The endothelial changes were also not typical of keratitic precipitates. Proteinaceous deposits have been seen in patients with uveitis such as those with Fuchs’ endothelial dystrophy as well as in patients with PXF . There did not appear to be a direct correlation between PXF and the changes we saw in our small study.…”
Section: Discussioncontrasting
confidence: 60%
“…The endothelial changes were also not typical of keratitic precipitates. Proteinaceous deposits have been seen in patients with uveitis such as those with Fuchs’ endothelial dystrophy as well as in patients with PXF . There did not appear to be a direct correlation between PXF and the changes we saw in our small study.…”
Section: Discussioncontrasting
confidence: 60%
“…We found no correlation between amount of inflammatory cells in the AC and numbers of DLCs (the four-step grading system may be too rough to detect a correlation). Mocan et al 20 reported that the eight patients with keratouveitis had ≥2 cells in the AC, but do not show mean or maximum AC cell readings and no correlation with presence and numbers of inflammatory cells in the cornea.…”
Section: Discussionmentioning
confidence: 98%
“…The mean density of these keratic precipitates was 16.01 ± 6.54 keratic precipitates/mm 2 . Subsequent studies using slit scanning IVCM showed multiple morphologies, the most common being dendritiform (85%, 77.5%), stippled (67.5%, 58.3) and globular (85%, 27.8%).…”
Section: Distinguishing Infective Vs Non‐infective Causes Of Uveitismentioning
confidence: 99%